Actual measuring technologies of Industry 4.0 and analysis of their realization experience. (November 2019) - Taymanov, R; Pronin, A; Sapozhnikova, K; Baksheyeva, Iu; Danilova, I
Abstract: Civilization development requires a multifold increase in the volume of measuring information. Such an increase, to a significant extent, is caused by the necessity to solve qualitatively new measuring tasks. To meet this need is possible by the transition to new measuring technologies. The experience of the D.I. Mendeleyev Institute for Metrology in developing actual technologies, in particular, metrological self-check and virtual tests, proves their efficiency and discloses realization features.